A Study on Politeness Strategies in the Conversations of the Course Book “Topnotch 2” Pre-intermediate (the First Edition = Nghiên cứu về chiến lược lịch sự trong các bài hội thoại của giáo trình giao tiếp “Top Notch 2” Pre-intermediate (phiên bản đầu tiê - Vũ, Thị Thanh Huyền, 1987- (University of Languages and International Studies, 2017)
It is undeniable that English nowadays has become indispensable means of international communication. However, there are still a large number of Vietnamese EFL learners who have not achieved success in using English in their communication since they may face difficulty understanding the content of conversation or expressing exactly what they mean. One of the significant factors necessary for students to get more successful in English conversations is the awareness of politeness strategieswhich are implicitly introduced in textbooks.The study is conducted using descriptive qualitative research method to find out politeness strategies in the course book “Top Notch 2” (the First Edition). In order to fulfill these aims, the author picked up 150utterances from the sound bites and the conservation models in the course book to analyze in the light of politeness theory proposed by Brown and Levinson (1978, 1987). The findings and results of the study show that most of negative and positive politeness strategies are found in the conversations and among them positive politeness strategies 4, 5 and 2, negative politeness strategies 2, 1, and 6 are most frequently used. In addition, the author also would like to offer some useful implications for effective teaching of positive and negative politeness strategies